(ii) Hemiarthroplasty of the glenohumeral joint. Issue 5 (October 2015) - Ibrahim, Edward; Thomas, Michael
Abstract: Hemiarthroplasty of the humeral head is indicated for glenohumeral arthritis unresponsive to conservative measures and for some acute fractures of the proximal humerus. Regardless of indication, the functional result relies upon recreation of normal anatomy. In the elective setting, stemmed, stemless and surface replacement prostheses are available. Significant controversy exists regarding implant choice, and a longstanding debate concerning the choice of hemiarthroplasty versus total shoulder replacement continues. Complex fractures of the proximal humerus may not be reconstructable or may place the humeral head at excessive risk of avascular necrosis. Stemmed prosthetic replacement is often performed for such indications. This is a technically challenging procedure for which results are related to the healing of the bony tuberosities which in turn provides best rotator cuff function. Tuberosity healing is though to be related to good surgical technique. This article aims to review the history, indications, technique and results of prosthetic hemiarthroplasty of the shoulder. Where available, comparison of results is made with alternative prosthesis designs and with other available forms of glenohumeral arthroplasty for each indication.